Hemophagocytic Histiocytic Sarcoma in Dog - Goulart, Juliana das Chagas; Sanches, Felipe Jacques; Merlini, Natalie Bertelis; Mazzucatto, Barbara Cristina; Gasser, Beatriz; Marcusso, Paulo Fernandes (Acta Scientiae Veterinariae, 2020)
Background: Histiocytic sarcoma can present in a localized or disseminated form, being a malignant neoplasm derived from interstitial dendritic cells. Another form of the disease is called hemophagocytic histiocystic sarcoma (HHS), which originates from macrophages located in the splenic red pulp and bone marrow. HHS is a rare neoplasm with unknown etiology and rapid development. It mainly affects middle-aged to elderly animals. It primarily affects the spleen and bone marrow, with occurence of metastases in other organs. Some canine breeds are considered more predisposed to this neoplasia, among them the Rottweiler. The aim of this study was to report a case of HHS in a Rottweiler dog. Case: An 8-year-old Rottweiler suffering from hyporexia and progressive weight loss for a month was attended at the Veterinary Hospital of State University of Maringá. On physical examination, he only presented mild discomfort on abdominal palpation. Blood count was performed, which revealed mild thrombocytopenia (145,000/µL, reference value for the species 150,000-500,000/µL). The Polymerase Chain Reaction (PCR) exam was requested for babesiosis and ehrlichiosis, due to a history of ectoparasites. The animal was released with the prescription of Doxycycline at a dose of 10 mg/kg orally for 28 days. After 5 days, the condition worsened and the animal returned with emesis, apathy and hyporexia, being hospitalized. Abdominal ultrasound, blood count, urinalysis, serum urea and creatinine tests were requested. Among the hematological changes, thrombocytopenia (116,000/µL) and the appearing of regenerative anemia and atypical round cells with ample and slightly basophilic cytoplasm in the smear, similar to histiocytes, stood out. On ultrasound examination, splenomegaly was observed with hypoechogenic areas. Ultrasound-guided fine-needle aspiration cytology (FNAC) of the spleen was performed, which revealed the presence of abundant cellularity consisting of round cells arranged individually and in small groups, with variable nucleus / cytoplasm ratio, slightly basophilic cytoplasm and, sometimes, vacuolized. Eccentric nucleus with chromatin ranging from loose to dense, with evident and often multiple nucleus. In addition, a large number of multinucleated giant cells, mitosis figures (sometimes atypical) and intense anisocytosis and anisocariosis were observed. Furthermore, it was possible to observe erythrophagocytic activity, alterations compatible with histiocytic sarcoma (HS). After 10 days of the first visit, the animal died. At necropsy, samples from altered areas of the spleen, lungs and lymph nodes were collected and sent for histopathological and immunohistochemical examination, in which the diagnosis of hemophagic histiocytic sarcoma was confirmed, in addition to lungs and lymph node metastasis. Discussion: The prognosis of HHS is the worst among histiocytic disorders, as it is associated with coagulopathies and severe anemia due to erythrophagocytic activity, as occurred in the case presented, with a maximum survival time between one to two months. The described animal died ten days after showing the first clinical signs. The immunohistochemistry technique using HLA-DR, CD18, CD163, and CD11d markers was essential to confirm the cell line. Positivity for CD11d marker was found, which allowed to classify the neoplasm as hemophagocytic HS. This report exposes the importance of cytological examination for screening and histopathological and immunohistochemical tests to confirm the diagnosis of this extremely aggressive neoplasm.